Fictions industrielles et apprentissage du temps : les jeux LEGO Bionicles - Irène Langlet (Strenae)
There is a LEGO paradox: the Danish firm arrived late to the scene, concerning new multimedia and digital toys, yet nevertheless released one of the most exemplary products of the 2000s: the Bionicle line, mixing figurines, construction games, popular multi-media fictions (in print, television, video games, CD-Rom, and cinema), communities of online players, shared universes, and all of the derivative non-gaming products. A detailed description of the Bionicle line immediately reveals not only its close adaptations arising from problems of intermedia permeability and the exploitation of fiction, but also its major innovation, closely linked to the nature of the LEGO firm's products. After several generalized themed series stimulating the imagination, this line accomplished, through the process of "mediatization," the transition of LEGO to narrativization. We will show how introducing narrative to this line aligned with the main industry goal of media-related consumer goods: consuming media is itself still part of playing the core game. But we will also see how this narrative framework can prompt analyses that go beyond marketing theory or toy instruction, which have to do with the contemporary uses of fiction and with developmental psychology in terms of mastering temporality.